Elementary school teacher’s perceptions of stem-based performance assessment across urban and rural contexts - Tiani Nabillah; Ghullam Hamdu; Agnestasia Ramadhani Putri (Universitas Negeri Surabaya, 2025)
This study aims to analyze elementary school teacher’s perceptions of the use of This study investigates elementary teacher’s perceptions of STEM based performance assessment and examines how these perceptions vary between urban and rural school settings. The study adopts a descriptive mixed methods design in which quantitative survey findings serve as the main source of analysis and qualitative input is used to clarify contextual differences across geographical locations. A total of 52 teachers completed a 12 item questionnaire measuring awareness, familiarity, and fluency, followed by short interviews with a purposive sample to explore the reasons behind emerging patterns. The results show that all three aspects fall within the high category, indicating that teachers view STEM based performance assessment as valuable for supporting critical thinking, creativity, collaboration, and problem solving. Fluency receives the highest mean score, suggesting that many teachers feel reasonably confident implementing STEM assessment, although the qualitative data reveal gaps in rubric design and project based assessment skills. The comparison across locations shows that rural teachers consistently report higher perceptions than urban teachers. Rural teachers describe more contextual and community oriented experiences, while urban teachers highlight administrative barriers and limited access to technical training. The findings underscore the need for professional development that is sensitive to geographical conditions and supports teachers in designing authentic, integrated STEM performance assessments.